PENGARUH MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE INDEKS CARD MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI NGORO JOMBANG - Nur, Madaniyah; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract: : The use of learning models plays a fairly important role in achieving the expected learning objectives. Through various learning models, it can foster a sense of interest and enthusiasm of students in following the learning process so that maximum learning outcomes are achieved. Finding out how the Index Card Match (ICM) cooperative learning approach affects student learning results in Islamic Religious Education (PAI) courses at SMA Negeri Ngoro Jombang is the goal of this study.This study uses employed a Quasi experiment nonequivalent Group and quantitative approach. Observation, testing, and documentation were employed for data collection, and SPSS version 23 was used for data analysis using the t-test, normality, and homogeneity tests. A higher average posttest score in the experimental class (79.17) than in the control class (71.67) demonstrated a substantial impact of the ICM model on student learning outcomes, and the t-test findings revealed a significance of 0.001 (<0.05). thus, The ICM learning model paradigm succeeded in improving student learning achievement in Islamic Religious Education subjects at Ngoro State High School, Jombang.